2000
DOI: 10.2172/782526
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the relationship between environmental forcing and the structure and dynamics of tornado-like vortices

Abstract: Axisymmetric numerical simulations continue to provide insight into how the structure, dynamics, and maximum windspeeds of tornadoes, and other convectively-maintained vortices, are influenced by the surrounding environment. This work is continued with a new numerical model of axisymmetric incompresible flow that incorporates adaptive mesh refinement. The model dynamically increases or decreases the resolution in regions of interest as determined by a specified refinement criterion. Here, the criterion used is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…23, 24, and 25). Additional high-resolution simulations by Nolan et al (2000), using an adaptivemesh-refinement technique, confirmed these results.…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…23, 24, and 25). Additional high-resolution simulations by Nolan et al (2000), using an adaptivemesh-refinement technique, confirmed these results.…”
Section: Introductionsupporting
confidence: 58%
“…Admittedly, the interpretation of S as a swirl ratio is problematic, as there is no guarantee that ⍀*L is indicative of the azimuthal velocity in the far field, because by (2.10) L is the height of the domain. It does not necessarily indicate the distance from which fluid travels to arrive in the core of the vortex [although this was indeed the case for Fiedler (1993) and Nolan and Farrell (1999), as the height and width of the convective forcing was matched to the size of the domain in those studies].…”
Section: ͑214͒mentioning
confidence: 98%
See 3 more Smart Citations